Relational dynamics between psychotherapy clients and clinic administrative staff: A pilot study. Issue 3 (3rd July 2017) - Sandage, Steven J.; Moon, Sarah H.; Rupert, David; Paine, David R.; Ruffing, Elizabeth G.; Kehoe, Lauren E.; Bronstein, Miriam; Hassen, Sarah C.
Abstract : Extensive empirical research has established therapeutic alliance as one of the most stable predictors of psychotherapy outcomes. Nearly all the contemporary empirical literature on therapeutic alliance focuses on the therapist-client dyad without attending to the relational experiences many clients in outpatient clinics have with administrative staff. Literatures from the fields of social work, psychiatric nursing and milieu therapy suggest there are more systemic relational and environmental dynamics that impact treatment beyond the therapist-client dyad, although these issues have been considered primarily in inpatient settings. A relational ecology framework has been developed drawing upon relational psychoanalysis, attachment theory and symbolic anthropology to help conceptualise the broader relational dynamics beyond the therapist-client dyad that may impact a more systemic therapeutic alliance in certain outpatient contexts. In an initial cross-sectional pilot study with a sample of clients ( N  = 107) receiving psychotherapy at a community mental health clinic in the Northeastern United States, the present study found client ratings of both (a) the therapeutic alliance with their therapists and (b) their alliance with administrative staff each significantly positively predicted client ratings of treatment. Thus, ratings of administrative alliance predicted client ratings of treatment over and above the effects of the therapist-client therapeutic alliance. These findings provide preliminary support for further investigation of the relational ecology of outpatient psychotherapy and suggest that client experiences of relational and environmental dynamics with administrative staff may be important contributors to psychotherapy outcomes. Limitations of the present study and implications for future research and practice are discussed.